The Effect of Adding Carrot Puree on Organoleptic and Chemical Properties of Dodol - Nada Risna Diya; Erwandi Erwandi (JAND: Journal of Applied Nutrition and Dietetic, 2022)
Dodol is a processed food made from a mixture of glutinous rice flour, sugar, sand, and coconut milk which is boiled until it becomes thick, oily, and not sticky. Carrots are not only rich in fiber and beta carotene, but also have a distinctive color that can be used as a natural dye in lunkhead.  Often the food production in circulation uses artificial coloring, but with the addition of carrots, it is possible to reduce the use of chemical dyes and add nutritional value to food, especially in processed carrots.  Objectives (1) To determine the effect of adding 100 gr, 125 gr, 150 gr carrot puree on the organoleptic and chemical properties of dodol. This study was experimental, with a non-factorial completely randomized design (CRD) with 3 treatments and 3 repetitions. This research was conducted to see the effect of adding carrot puree to the organoleptic and chemical properties of lunkhead.  The results showed that the addition of 100 gr, 125 gr, 150 gr carrot puree on the organoleptic and chemical properties of lunkhead.  significantly affected the taste and color of dodol (p value < 0.05) and the results of the carbohydrate test, ash content, water content significantly affected the effect of adding carrot puree to the organoleptic and chemical properties of dodol (p value < 0.05).  The results of the acceptability analysis of dodol with the addition of carrot puree were found to have a significant effect on the color of dodol and the taste of dodol.  No significant effect on the aroma of dodol and the texture of dodol.  Based on the results of the chemical test, the highest average carbohydrate value was found in the third treatment with the addition of 150 g of carrot puree.